Multiparty quantum contract signing - Liu, Zi-Fan; Yang, Rui-Jie; Cai, Xiao-Qiu; Wang, Tian-Yin (Frontiers in Physics, 2023)
Quantum contract signing has the advantage of unconditional security compared with classical one. However, the prior works focus on two clients' case. In this paper, we give a multiparty quantum contract signing protocol, which allows multiparty clients to sign an electronic contract simultaneously. The analysis shows that it not only satisfies the requirements for optimism and fairness but also can be realized with current technology.